Effectiveness of percutaneous flexor tenotomies for the management and prevention of recurrence of diabetic toe ulcers: a systematic review. Issue 1 (December 2016) - Scott, Jennifer; Hendry, Gordon; Locke, John
Abstract Background Diabetic toe ulcers are a potentially devastating complication of diabetes. In recent years, the percutaneous flexor tenotomy procedure for the correction of flexible claw and hammer-toe contraction deformities has been proposed as a safe and effective technique for facilitating the healing of toe-deformity related diabetic ulcers. The aim of this review is to critically appraise the evidence for the effectiveness of this surgical procedure in achieving ulcer healing, prevention of re-ulceration, and to summarise the rate of post-operative complications. Method A search of medical databases, was performed to locate relevant literature. Titles were screened prior to abstract and full text review to identify articles relevant to the research question. Search terms included truncations of "tenotomy", "toe", "hallux", "digit", "diabetes" and "ulcer". Peer reviewed primary research study designs specified as suitable for systematic reviews by the Centre for Reviews and Dissemination were included. Studies were excluded if they used a concurrent secondary procedure or included non-diabetic patients without reporting outcomes separately. Included studies were appraised for quality using the Methodological Index for Non-Randomised Studies tool. Levels of evidence were subsequently assigned to each outcome of interest (healing rate and prevention of re-ulceration). Results From a total search yield of 42 articles, 5 eligible studies (all case series designs) were identified for inclusion. Included studies were of low-to-moderate methodological quality when assessed using the MINORS tool. A total of 250 flexor tenotomy procedures were performed in a total of 163 patients. Included studies generally reported good healing rates (92–100 % within 2 months) post-op follow-up), relatively few recurrences (0–18 % at 22 months median post-op follow-up), and low incidences of infection or new deformity. Transfer ulcers developing on adjacent areas as a result of shifted pressure were reported by several authors. The validity of these results is undermined by methodological limitations inherent to case series designs such as a lack of control groups, non-randomised designs, as well as inconsistent reporting of post-intervention follow-up periods. There was level 4 evidence for the flexor tenotomy procedure in facilitating ulcer healing and preventing re-ulceration. Conclusion More definitive research evidence is needed in this area to determine whether or not the flexor tenotomy is a safe and effective treatment option for people with, or at risk of developing diabetic toe ulcers. Whilst the available literature reports that the procedure may be associated with high healing rates, relatively low recurrence rates and low incidences of post-op complications, methodological limitations restrict the value of these findings.